Search for the baryon- and lepton-number violating decays B0→pμ− and B0s→pμ− - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Borsato, Martino; Caspary, Rowina; Frau, Giulia; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; Leverington, Blake; Li, Peilian; et al. (Physical review, 2023)
A search for the baryon- and lepton-number violating decays B0→pμ− and B0s→pμ− is performed at the LHCb experiment using data collected in proton-proton collisions at √s=7, 8 and 13 TeV, corresponding to integrated luminosities of 1, 2, and 6 fb−1, respectively. No significant signal for B0→pμ− and B0s→pμ− decays is found and the upper limits on the branching fractions are determined to be B(B0→pμ−)<2.6(3.1)×10−9 and B(B0s→pμ−)<12.1(14.0)×10−9, respectively, at 90% (95%) confidence level. These are the first limits on these decays to date.